2022
DOI: 10.1111/pbi.13772
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐tuning of SUMOylation modulates drought tolerance of apple

Abstract: Summary SUMOylation is involved in various aspects of plant biology, including drought stress. However, the relationship between SUMOylation and drought stress tolerance is complex; whether SUMOylation has a crosstalk with ubiquitination in response to drought stress remains largely unclear. In this study, we found that both increased and decreased SUMOylation led to increased survival of apple ( Malus × domestica ) under drought stress: both transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 88 publications
1
17
0
Order By: Relevance
“…MdDREB2A was mainly expressed in roots and leaves and was induced by PEG6000 (Figure ). Subsequently, MdDREB2A ‐overexpressing apple seedlings ( MdDREB2A OE ) were obtained (Figure ), which showed improved resistance to drought stress compared to those exposed to adequate water levels (Figure 2a; Li et al, 2022). MdDREB2A OE showed increased NIR activity and total nitrogen content in both shoots and roots under drought conditions compared to the wild‐type (Figure 2b–e).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…MdDREB2A was mainly expressed in roots and leaves and was induced by PEG6000 (Figure ). Subsequently, MdDREB2A ‐overexpressing apple seedlings ( MdDREB2A OE ) were obtained (Figure ), which showed improved resistance to drought stress compared to those exposed to adequate water levels (Figure 2a; Li et al, 2022). MdDREB2A OE showed increased NIR activity and total nitrogen content in both shoots and roots under drought conditions compared to the wild‐type (Figure 2b–e).…”
Section: Resultsmentioning
confidence: 99%
“…The protein stability of DREB2A in Arabidopsis is finely regulated under environmental stress. For example, MdRNF4 mediates the degradation of SUMOylated MdDREB2A via ubiquitination under drought conditions (Li et al, 2022). In this study, the GFP fluorescence signal was significantly induced by nitrate (Figure ), suggesting posttranslational regulation of MdDREB2A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies on Malus domestica evidenced the implication of SUMOylation in regulating DREB2A stability as a critical determinant of drought tolerance. Interestingly, it was reported that drought tolerance in apples involves a complex network of increased and reduced levels of SUMOylation and ubiquitination, respectively, where SUMOylated MdDREB2A serves as a target for RNF4-mediated ubiquitination and degradation (Li et al, 2022 ). Pepper dehydration-responsive homeobox1 domain (CaDRHB1) TF serves as a positive regulator of the desiccation stress response.…”
Section: Sumoylationmentioning
confidence: 99%